Catching up by hiring: The case of Huawei - Kerstin J. Schaefer (Journal of International Business Studies, 2020)
Hiring experts in centers of state-of-the-art technology is an important way in which a multinational enterprise (MNE) can gain competitive advantage, and yet use of this mechanism remains under-researched. This study uses the case of a Chinese MNE that recently achieved a leading position in the telecommunications market: Huawei Technologies. Taking the perspective of Huawei's offshore hires, I find that greenfield investments contributed to overcoming liabilities of origin and outsidership in the global telecommunications industry. Nevertheless, even now that Huawei has caught up with industry incumbents, its output capabilities remain dependent on the innovation capabilities of its offshore experts.
Keywords: 330; R&D internationalization; latecomer companies; catching up by hiring; innovation capabilities; greenfield investment; emerging market multi-nationals